EFEKTIVITAS PENERAPAN MODEL RECIPROCAL TEACHING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA - Pertiwi, Peni; Elindra, Rahmatika; Ahmad, Marzuki (JURNAL MathEdu (Mathematic Education Journal), 2023)
Abstract This study aims to determine the effectiveness of the application of the Reciprocal Teaching model on the mathematical critical thinking skills of MTs students. Al-Abraar. This type of research is experimental research, with the entire population of class VIII MTs students. Al-Abraar as many as 102 students. The sample of this research is class VIII C, totaling 28 students using simple random sampling technique. Data collection uses observations and tests that have been previously validated. The results showed an overview of the reciprocal teaching learning model with an average value of 3.30 with a "good" category describing students' mathematical critical thinking skills before using the reciprocal teaching learning model, the average value was 52.36 with the "less" category. Meanwhile, for students' mathematical critical thinking skills after using the reciprocal teaching learning model, an average value of 83.33 was obtained with the "very good" category, in other words there was an increase in the use of the reciprocal teaching learning model on students' mathematical critical thinking skills. And based on the significant T-test 0.000 < 0,05, it means that the alternative hypothesis formulated in this study is acceted or approved. This means that the reciprocal teaching learning model is effective in improving students' mathematical critical thinking skills in MTs. Al-Abraar. Keywords: Reciprocal Teaching, Critical Thinking Ability, Student Mathematics.